From social justice to landscapes: The politics behind the woodblock prints of See Cheen Tee / Eugene Foo Shyang Eu - Eugene Foo , Shyang Eu (2020)
See Cheen Tee produced over 50 pieces of woodblock prints in the mid-1950s to the mid-1960s. This research seeks to investigate the politics behind these woodblock prints by studying social and political climate of the time it was produced. Politics in this research must be understood in the context of power relations that includes both formal and informal, organizations or individuals, and is not limited to the generalized notion of the activities of governmental bodies. His work is compared and contrasted against other artworks such as woodblock prints produced during the Chinese Modern Woodcut Movement, paintings by first generation Nanyang-style artists and even some of his contemporaries. The research approaches his woodblock prints according to themes that are observed to be prevalent in the subject matter of the prints, namely Social Justice, visualizing nationhood, the exotic native Other, and feminine figures. This wide range of subject matter required several methodologies and theoretical frameworks to be consulted. This included social political historical data, Post-Colonial theory, the concepts of the Other, and also gender politics. The analyses of his works revealed that his early works were closely related to Social Justice themes, and engaged with formal politics and perceivable formal structures of power. But as his subject matters veered towards more genre scenes and landscapes, the workings of politics also delved into more personalized areas of informal politics, that deals with personal visions of nation-building, negotiating with native ethnicities as the other, and the gaze of the artist based on gender. See’s work demonstrates a sort of sensitivity to these subject matters that reveals an ambivalent quality. This research further dismantles the notion that woodblock prints are necessarily related to the workings of formal politics and that it is an equally pliable medium that allows for very unique representations capable of even creating fine nuances that convey more complex narratives.